The Responses of an End-Bearing Pile to Adjacent Multipropped Excavation: 3D Numerical Modelling - Mangnejo, Dildar Ali; Mangi, Naeem; Hemu, Hemu (Civil Engineering Journal, 2019)
It is well recognised that superstructure load is transferred to surrounding soil through piled foundation. Consequently, the high stress regime (stress bulb) is generated surrounding of the pile. On the other hand, the excavation in the ground inevitably results in the ground movement due to induced-stress release. These excavations are sometimes inevitable to be constructed adjacent to existing piled foundations. This condition leads to a big challenge for engineers to assess and protect the integrity of piled foundation. This research presents three-dimensional coupled consolidation analyses (using clay hypoplastic constitutive model which takes account of small-strain stiffness) to investigate the responses of an end-bearing pile due to adjacent excavation at different depths in soft clay. The effects of excavation depths (i.e., formation level) relative to pile were investigated by simulating the excavation near the pile shaft (i.e., case S) and next to (case T). It was revealed that the maximum induced bending moment in the pile after completion of excavation in all the cases is much less than the pile bending moment capacity (i.e. 800 kNm). Comparing the induced deflection of the end-bearing pile in the case T, the pile deflection in case S is higher. Moreover the piles in cases of S and T were subjected to significant dragload due to negative skin friction.